RAISING OF PEDAGOGICAL MASTERY OF A TEACHER OF LITERATURE IN THE SYSTEM OF AFTER DEGREE EDUCATION AS A SCIENTIFIC PROBLEM - L.O. Reshetnyak (Academy of Cognitive and Natural Sciences, 2022)
The article is dedicated to one of actual questions of modern theory and practice of professional education - raising of pedagogical mastery of a teacher of literature in the system of after degree education.